Depression and Anxiety as Risk Factors for Delayed Care-Seeking Behavior in Human Immunodeficiency Virus–Infected Individuals in South Africa. (12th April 2018) - Rane, Madhura S; Hong, Ting; Govere, Sabina; Thulare, Hilary; Moosa, Mahomed-Yunus; Celum, Connie; Drain, Paul K
Abstract : Depression and anxiety are associated with delayed presentation to HIV care but not late testing in South Africa. Interventions aimed at improving engagement in HIV care should consider screening for depression and anxiety when patients first present for HIV testing. Abstract: Background: Facility- and community-based efforts to improve human immunodeficiency virus (HIV) testing in sub-Saharan Africa may benefit from understanding how mental health influences HIV care-seeking behavior. Methods: We conducted a study among adults presenting for HIV testing in the Umlazi township of South Africa. Prior to testing, we measured depression using the 9-item Patient Health Questionnaire and anxiety using the 7-item Generalized Anxiety Disorder scale. We categorized patients as delayed presenters (presenting to clinic >3 months after first HIV-positive test), late testers (presenting within 3 months of diagnosis with a CD4 count ≤200 cells per µL), or neither. We used multinomial logistic regression adjusting for sociodemographic and behavioral characteristics to determine the effects of depression and anxiety on HIV care-seeking behavior. Results: Among 1482 HIV-infected adults, 59% were female and mean age was 33 years. The prevalence of depression in the cohort was 33% and anxiety was 9%. In adjusted models, mild to moderate depression was not associated with delayed presentation or late testing. HIV-infected adults with severe depression had 3.6 greater odds (95% confidence interval [CI], 1.2–10.2) of delayed presentation and 2.2 greater odds (95% CI, 1.01–4.8) of late testing compared with those without depression. Individuals with generalized anxiety had 2.3 greater odds (95% CI, 1.3–4.2) of delayed presentation compared with those without anxiety. Conclusions: Severe depression was associated with delayed presentation and late testing, while anxiety was associated only with delayed presentation. Screening for mental health services may improve antiretroviral therapy initiation and linkage to care following HIV testing.